2019
DOI: 10.1039/c9cp02368b
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular interactions and solvation effects of dimethylsulfoxide on type III deep eutectic solvents

Abstract: Intermolecular interactions within the mixtures of DMSO and reline, a typical type III Deep Eutectic Solvent (DES), composed of urea and choline chloride, is examined along with the mixtures' physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…A detailed comparison of density data for neat reline available in the literature can be found elsewhere. 20 Figure 1b compares the ρ(x 1 ) data obtained in this study at 298.15 K with those of Shah et al 17 As noted above, we investigated only a limited number of samples at this temperature (Table S1 of the Supporting Information) due to the tendency of some of the prepared mixtures to precipitate. According to Figure 1b, the present ρ(x 1 ) data are generally somewhat larger than those of ref 17, but they follow the same trend.…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…A detailed comparison of density data for neat reline available in the literature can be found elsewhere. 20 Figure 1b compares the ρ(x 1 ) data obtained in this study at 298.15 K with those of Shah et al 17 As noted above, we investigated only a limited number of samples at this temperature (Table S1 of the Supporting Information) due to the tendency of some of the prepared mixtures to precipitate. According to Figure 1b, the present ρ(x 1 ) data are generally somewhat larger than those of ref 17, but they follow the same trend.…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…Similarly, mixtures of [Ch] + [Cl] − , urea and DMSO have been studied by Shah et al . with MD simulations [40] . It was found that the number of H‐bonds between urea and DMSO became significant at DMSO fractions higher than 70 %.…”
Section: Introductionmentioning
confidence: 98%
“…Fuelled by searching for environmentally friendly solvents for sustainable chemical processes, deep eutectic solvents (DESs) have emerged as green designer solvents with a wide range of applications. A typical DES consists of an HB acceptor (HBA) and an HB donor (HBD), mixed in the eutectic molar ratio. , DES nanostructures, stabilized by intercomponent HB interactions, can be further tuned by the addition of cosolvents capable of disrupting the native HB networks. As water can act as both HBA and HBD, these neoteric solvents are highly water-miscible and hygroscopic. , Recent reports demonstrate that water addition in the eutectic mixtures influences the DES nanostructures and consequently impacts their physicochemical properties . Trends in these properties suggest an upper limit of DES hydration, above which DES behaves like an aqueous solution. …”
mentioning
confidence: 99%